Materialistic cues make us miserable: A meta‐analysis of the experimental evidence for the effects of materialism on individual and societal well‐being. Issue 10 (21st June 2020) - Moldes, Olaya; Ku, Lisbeth
Abstract: Consumer‐oriented societies are awash with materialistic messages that link happiness and success to wealth and consumption. However, despite extensive research evidence that dispositional materialistic orientations are correlated with lower well‐being, the effects of materialistic cues on the well‐being of individuals and social groups have not been examined. The present research meta‐analytically reviews the experimental evidence for the causal effects of materialism on two dimensions of well‐being: (a) individual and (b) societal. We included 27 independent studies that met the inclusion criteria of priming materialism and measuring well‐being ( N  = 3, 649), containing a total of 62 effect sizes. Multilevel modeling revealed that materialism has an effect on both individual ( δ  = −0.39) and societal well‐being ( δ  = −0.41), suggesting that materialistic cues cause lower well‐being. Moderation effects suggested that materialistic cues might have a higher effect on interpersonal well‐being than on self‐evaluation indicators. We discuss the limitations of the current evidence, highlight the research gaps and underdeveloped areas, and provide recommendations such as minimum sample size for future experimental work, since the advancement of this area will help us to gain a better understanding of the impact of consumer‐oriented societies on the well‐being of individuals and social groups.